PENGARUH ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL DISCLOSURE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Rafly Ardiansyah (2022)
This study aims to determine whether there is an influence of environmental performance, environmental disclosure, and corporate social responsibility on financial performance. This study sets a sample of state-owned companies registered in the territory of the Republic of Indonesia. The research sample was taken using the census sampling technique. The hypothesis testing tool used in this study is SPSS version 16 with a significance level of 5% or 0.05. The tests carried out to analyze the research data were descriptive statistical tests, normal distribution tests, multicollinearity tests, autocorrelation tests, regression analysis tests, and t tests. The results show that environmental performance and environmental disclosure have no effect on financial performance. On the other hand, corporate social responsibility has a negative influence on financial performance.